Enhancing Criminal Investigation Through the Use of Closed Circuit Television in Brgy. Mapulang Lupa: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Criminal activities are on the rise globally, and they're becoming a threat to the safety andsecurity of residents in urban and rural areas. The use of closed-circuit television (CCTV)technology is an effective way of enhancing criminal investigation and preventing crime inpublic spaces. The barangay Mapulang Lupa has been experiencing an increase in criminalactivities, prompting the need for the use of CCTV technology to monitor and deter criminalactivities. This study aims to explore the potential of CCTV technology in enhancing criminalinvestigations in barangay Mapulang Lupa.The study findings revealed that the use of CCTV technology has a positive impact onenhancing criminal investigations in Barangay Mapulang Lupa. The majority ofcorrespondents believed that the installation of CCTV systems led to a reduction in crimerates in the area. CCTV technology has also helped in identifying and prosecuting criminals ofcorrespondents, indicating that the technology plays a significant role in criminalinvestigations. Additionally, CCTV has a deterrent effect on criminal activities ofcorrespondents reporting a decrease in vandalism, theft, and other offenses in areas withCCTV cameras. Furthermore, the study findings showed that CCTV technology has helped toenhance public safety and reduce fear among residents.The study concludes that CCTV technology has significant potential to enhance criminalinvestigations in Barangay Mapulang Lupa. Technology has a positive impact on crimeprevention, identification, and prosecution of criminals. CCTV technology has also beenshown to have a deterrent effect on criminal activities, making public spaces safer forresidents. The study recommends that the local government and law enforcement agenciescontinue to invest in CCTV systems and implement policies and procedures that maximize theeffectiveness of this technology in crime prevention and investigation.
Keywords: Criminology